Evaluation on the effect of the transformation policy of resource-exhausted cities—An empirical analysis based on the difference-in-difference model - Bin Yang; Xiaoyi Zhan; Yihao Tian (Energy Reports, 2021)
Realizing the effective transformation of resource-exhausted cities and promoting the sustainable development of these cities are part of high-quality economic development. From 2004, China promulgated a series of policies on promoting the sustainable development of resource-based cities. It is of great significance to objectively evaluate the effects of the polices for the implementation and improvement of the policy itself. Based on the panel data of 284 prefecture-level cities in China from 2003 to 2018, this study uses the policies to constructs the heterogeneous timing difference-in-difference model to evaluate the impacts of transformation policies on the economic growth of resource-exhausted cities and found that the policies have a significant role in promoting the economic growth of resource-exhausted cities, which was verified by placebo test, showing that the policy is effective, and puts forward some suggestions for the further promotion of the transformation of resource-exhausted cities.